Bifidobacterias como indicadoras de contaminación fecal en aguas tropicales - Sarmiento-Rubiano, Luz Adriana (Universidad de Costa Rica, 2019)
Abstract. Human fecal pollution water is a serious risk to the public health, nevertheless the indicator microorganisms commonly used to assess the levels of fecal pollution not identify the specific source. The detection of certain species of the Bifidobacterium genus as B. adolescentis and B. dentium have been proposed as an effective marker of human fecal contamination but this has not been proved previously in tropical environmental conditions. For this study, sample and countersample of water were taken from the Mesolandia swamp of the Colombian Caribbean, as well as 260 samples of human feces and 94 samples of domestic animals feces were taken from a peripheral human settlement to the swamp. DNA extraction was performed from each of the samples taken and the Bifidobacteria profile was determined by the PCR-DGGE technique (denaturing gradient gel electrophoresis) using specific specie primers based on the 16S rRNA gene sequence primers, whose sequences were analyzed on the GenBank Database. After the analyzes performed, it was observed that eight species of Bifidobacterium that were found in the water, were also present in the human feces, of which B. adolescentis and B. dentium  considered as markers of human fecal pollution also were found in domestic animals. In this study, under the environmental and experimental conditions evaluated, it was not possible to find a specific specie of bifidobacteria of the human intestine as marker of human fecal contamination in tropical environments. However, the applied method allowed a closer approximation to the origin of the fecal contamination in relation to the traditional culture methods, since it was possible to find specific DNA sequences in the water identical to those on the fecal samples studied.  La contaminación fecal humana en el agua constituye un importante riesgo para la salud pública, sin embargo, los microorganismos indicadores comúnmente utilizados para detectar contaminación fecal no identifican su fuente específica. La detección de ciertas especies del género Bifidobacterium como B. adolescentis y B. dentium ha sido propuesta como un efectivo marcador de contaminación fecal humana, pero esto no ha sido evaluado en las condiciones ambientales tropicales. El objetivo de este trabajo fue determinar el perfil de bifidobacterias, en una muestra de agua de la Ciénaga de Mesolandia en el Caribe Colombiano y en 260 muestras fecales humanas y 94 de animales domésticos de un asentamiento humano periférico a la ciénaga. El ADN extraído de cada una de las muestras fue amplificado por PCR mediante el uso de cebadores específicos de género basados en la secuencia del gen 16S ARNr y separados por DGGE (Electroforesis en Gel con Gradiente Desnaturalizante). Las bandas obtenidas en DGGE, fueron extraídas del gel, re-amplificadas, secuenciadas y las secuencias comparadas con la base de datos del GenBank. El perfil de bifidobacterias en DGGE mostró la presencia de ocho especies de Bifidobacterias en la muestra de agua, las cuales también fueron identificadas en las heces humanas. B. adolescentis y B. dentium propuestas como marcadores de contaminación fecal humana, también fueron encontradas en animales domésticos. En este estudio bajo las condiciones ambientales y experimentales evaluadas no fue posible encontrar una especie de Bifidobacteria específica para ser utilizada como marcador de contaminación fecal humana en ambientes tropicales. Sin embargo, el método aplicado permitió una aproximación más cercana al origen de la contaminación fecal en relación con los métodos culturales tradicionales, ya que fue posible encontrar secuencias de ADN idénticas en el agua y en las muestras fecales.